Thermal comfort investigation in traditional and modern urban canyons in Bandar Abbas, Iran - Dalman, Masoud; Salleh, Elias; Sapian, Abdul Razak; Saadatian, Omidreza (UPM Press, 2013)
Urban design plays an important role in a city’s daily life. Therefore, accessibility to thermal comfort spaces for citizens engaged in urban outdoor activities could be one of the main goals of urban designers. Urban forms and canyons have important roles in microclimate and thermal comfort situation in outdoor spaces. The hot humid climate of Bandar Abbas, especially in long summers, causes thermal stress for urban activities. In this study, two different urban fabrics were investigated using thermal comfort and Computational Fluid Dynamics (CFD) methods. Eight provisional measuring points in the selected prevailing canyons were used to obtain the data. The results correlated with the effects of the urban canyon orientation to variation of the microclimate factors, and consequently, the thermal comfort situation in the hottest period of the year. In addition, the results also indicated that the traditional urban fabric is more thermally comfortable than the new residential urban fabric. According to field measurements, thermal comfort calculation and wind simulations, the canyons with the north-south direction present a better orientation for air circulation benefiting from the sea breezes as compared to the other canyon orientations. Hence, this study provides insights for urban designers and policy makers residing in the hot and humid climate in the Middle East.